Discourse segmentation and interaction - Garrido, Joaquín (Círculo de Lingüística Aplicada a la Comunicación, 2017)
In discourse segmentation, discourse units are based on dependance and constituency, and they incorporate properties of units in other approaches such as the utterance and the act. Elementary discourse units establish discourse relations by virtue of their topic sentence structure. Framing and hanging topics, as well as parenthetical expressions, fall ouside of the inner sentence topic hierarchy of aboutness-shifting, contrastive and familiar topics. It is shown in the interaction of a political cartoon and a journalistic column how elementary units build up complex ones, including both properties of discourse relations and properties of topic management and the represented lexical frames, in a dynamic discourse-construction model that assumes syntactic continuity from sentence to discourse. Higher units involve interaction between participants according to the type of text, such as the political cartoon or the column. It is further shown how text structure affects discourse: depending on positions of lexical units in text structure, lexical relations may override the results of the discourse construction process and thus the resulting discourse representations.